Dislexia y su influencia en el aprendizaje de los estudiantes de 5°, 6° y 7° año de educación básica de la Escuela Fiscal Mixta Morona Santiago, Recinto Panigón, Parroquia Pimocha, Cantón Babahoyo - Yansapanta Andagana, Ángel Oswaldo (2016)
This research work has been carried out in order to know about dyslexia and its influence on the learning of reading - writing students in 5th, 6th and 7th year of basic education of the Joint Public School Morona Santiago considering that there was dyslexic school which could be determined at the time of internships, so it was considered important to study this issue found that teachers, children are dyslexic, because they are not I trained to work with children who present these problems for this field study was conducted through a track where it was collecting data from what was observed at the time that teachers and students worked, subsequently reviewed the content showing us that a large important group of children have dyslexia, with information obtained carrying out a strategy guide begins to improve student dyslexia serve to help improve their academic performance